Analisis Tingkat Kepuasan Pelanggan Terhadap Kualitas Layanan Go-Food Di Wilayah JABODETABEK Menggunakan Metode Servqual Dan Importance Performance Analysis - Winaryanto, Amalia Putri; Wahyuni, Delia Tri Puspa; Soetadi, Johana Zia; Tsani, Rubby Rahman (FEB Universitas Sultan Ageng Tirtayasa, 2024)
This study analyzes the level of customer satisfaction with Go-Food service quality in the Jabodetabek area using the SERVQUAL and Importance-Performance Analysis (IPA) methods. Data was collected through a questionnaire distributed to 100 Go-Food user respondents in Jabodetabek. The analysis results show a Customer Satisfaction Index (CSI) value of 84.45%, indicating a very high level of customer satisfaction. The IPA diagram reveals that the dimensions of “assurance” and “empathy” are in quadrant I, indicating good performance and according to customer expectations. Meanwhile, the dimensions of “reliability” and “price” are in quadrant IV, indicating the need for improvement in the aspects of on-time delivery and pricing strategy. This research provides valuable insights for Go-Food to improve service quality, especially in terms of reliability and pricing strategy, and maintain excellence in the aspects of assurance and empathy to maintain high customer satisfaction in the future.